Exploring the Influence of Nursing Work Environment and Patient Safety Culture on Missed Nursing Care in Korea - Kyoung-Ja Kim; Moon Sook Yoo; Eun Ji Seo (Elsevier, 2018)
Purpose: This study aimed to explore the influence of nurse work environment and patient safety culture in hospital on instances of missed nursing care in South Korea. Methods: A cross-sectional design was used, in which a structured questionnaire was administered to 186 nurses working at a tertiary university hospital. Data were analyzed using descriptive statistics, t test or analysis of variance, Pearson correlation, and multiple regression analysis. Results: Missed nursing care was found to be correlated with clinical career, nursing work environment, and patient safety culture. The regression model explained approximately 30.3% of missed nursing care. Meanwhile, staffing and resource adequacy (β = −.31, p = .001), nurse manager ability, leadership and support of nurses (β = −.26, p = .004), clinical career (β = −.21, p = .004), and perception on patient safety culture within unit (β = −.19, p = .041) were determined to be influencing factors on missed nursing care. Conclusion: This study has significance as it suggested that missed nursing care is affected by work environment factors within unit. This means that missed nursing care is a unit outcome affected by nurse work environment factors and patient safety culture. Therefore, missed nursing care can be managed through the implementation of interventions that promote a positive nursing work environment and patient safety culture. Keywords: environment, nursing care, patient safety, quality of health care